New York-La Mancha: Migration and Queer Transnationality in the Work of Dionisio Cañas (XXI Century. Spanish Literature and Culture, 2024)
This article analyzes the migration experience of the poet and artist Dionisio Cañas as a queer man. His migration to New York in 1972, where he lived for more than three decades, allowed him to freely enjoy his non-normative sexuality, as well as to grow intellectually and professionally. At the same time, his poetry reveals a profound nostalgia for La Mancha, his native land, in addition to a critical view of the dehumanization in New York City. Upon his return to La Mancha in 2005, Cañas denaturalizes heteronormative national discourses to adopt a transnational identity that includes both Spanish and US realities, claiming that he feels like a nomad and that his home is not made up by one specific geographic place.
Keywords: Dionisio Cañas; poetry; queer migration; New York; La Mancha; transnationality